2021
DOI: 10.2147/ijgm.s331573
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Three-Gene-Based Diagnostic Signature for Hypertension in Pregnancy

Abstract: Background: Hypertensive disorders of pregnancy affect approximately 5-10% of all pregnancies, and this study aims to identify potential diagnostic signatures. Methods: We downloaded the mRNA profiles of GSE75010 (placenta samples) and GSE48424 (blood samples) datasets with or without hypertension in pregnancy from the Gene Expression Omnibus database. Differential expression analysis was performed on the placenta samples using limma package of R language. GO terms and KEGG pathways enrichment analyses were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…We analyzed the gene expression profiles of placenta samples between preeclampsia and controls, and 57 differentially expressed genes were identified. Consistent with published data, the results of enrichment of these DEGs confirm their involvement in the development of preeclampsia, such as HIF1-signaling pathway, MAPK signaling pathway, cytokine-cytokine receptor interaction, which suggest that Inflammation and oxidative stress is important in preeclampsia [ 22 , 23 ]. It has been widely accepted that Inflammation and oxidative stress are vital processes concerned with placental ischemia and hypoxia in the development of preeclampsia, and part of genes in HIF1-signaling pathway are closely related to inflammation and oxidative stress.…”
Section: Discussionsupporting
confidence: 88%
“…We analyzed the gene expression profiles of placenta samples between preeclampsia and controls, and 57 differentially expressed genes were identified. Consistent with published data, the results of enrichment of these DEGs confirm their involvement in the development of preeclampsia, such as HIF1-signaling pathway, MAPK signaling pathway, cytokine-cytokine receptor interaction, which suggest that Inflammation and oxidative stress is important in preeclampsia [ 22 , 23 ]. It has been widely accepted that Inflammation and oxidative stress are vital processes concerned with placental ischemia and hypoxia in the development of preeclampsia, and part of genes in HIF1-signaling pathway are closely related to inflammation and oxidative stress.…”
Section: Discussionsupporting
confidence: 88%
“…Several studies have shown that the increased levels of IGFBP1 expression facilitate the differentiation of endometrial stromal cells and have an important role in the establishment of pregnancy [ 27 , 28 ]. In addition, it allows the genetic diagnosis of hypertension in pregnancy [ 29 ]. ADCY8 is a member of the adenylate cyclase family and constitutes only a minor adenylated cyclic glucosyl methyl ether [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%